Perception of Universal Basic Income and its Perceived Consequences - Singh, Khujan; Kataria, Pooja (Indian Journal of Finance, 2024)
Purpose : The current study focused on understanding the perception of universal basic income (UBI) and its perceived consequences. We investigated this potential alternative program that would address the shortcomings and restrictions of the current welfare system. Methodology : Five variables were used which addressed a diverse spectrum of dimensions related to the perception of universal basic income. Furthermore, how this perception varies across different demographic groups was examined. A total of 432 respondents from Haryana were included in this study. Statistical techniques like exploratory factor analysis, t-test, one-way ANOVA, and Welch test were used to analyze the data. Findings : The findings of the study indicated that females and unemployed respondents were more inclined to support UBI and were less skeptical toward its moral consequences as compared to men and employed individuals. Furthermore, people with less income strongly supported the concept, but they were less optimistic about its moral consequences and believed that UBI might encourage people to be lazy and unproductive. Practical Implications : It was proposed that carrying out a large-scale pilot project can yield relevant information regarding the viability of universal basic income. The government may have a greater knowledge of how UBI could aid in resolving societal challenges, including poverty, unemployment, and inequality, through a thorough evaluation. Originality : The majority of previous research has been done on European countries. This study is the first to concentrate on how the UBI is viewed in the Indian setting.